Financial cost of hypertension in urban and rural tertiary health facilities in Southwest, Nigeria: A comparative cross-sectional study - Tope Michael Ipinnimo; Eyitayo Ebenezer Emmanuel; Motunrayo Temidayo Ipinnimo; Kehinde Hassan Agunbiade; Oladipupo Adekunle Ilesanmi (Wolters Kluwer Medknow Publications, 2023)
Background: The financial cost of hypertension could result in serious economic hardship for patients, their households, and the community. To assess and compare the direct and indirect cost of care for hypertension in urban and rural tertiary health facilities. Material and Methods: A comparative cross-sectional study was carried out in two tertiary health facilities which are located in urban and rural communities of the southwest, Nigeria. Four hundred and six (204 urban, 202 rural) hypertensive patients were selected from the health facilities using a systematic sampling technique. A pretested semi-structured, interviewer-administered questionnaire adapted from that used in a previous study was used for data collection. Information on biodata, and direct and indirect costs was collected. Data entry and analysis were done using IBM SPSS Statistics for Windows, Version 22.0. Results: More than half of the respondents were females (urban, 54.4%; rural, 53.5%) and in their middle age (45-64 years) (urban, 50.5%; rural, 51.0%). The monthly cost of care for hypertension was significantly higher in urban than in rural tertiary health facilities (urban, ₦19,703.26 [$54.73]; rural, ₦18,448.58 [$51.25]) (P < 0.001). There was a significant difference in the direct cost (urban, ₦15,835.54 [$43.99]; rural, ₦14,531.68 [$40.37]) (P < 0.001), although the indirect cost (urban, ₦3,867.72 [$10.74]; rural, ₦3,916.91 [$10.88]) (P = 0.540) did not show much difference between the groups. The cost of drugs/consumables and investigations contributed more than half (urban, 56.8%; rural, 58.8%) of the cost in both health facilities. Conclusion: The financial cost of hypertension was higher in the urban tertiary health facility; therefore, more government support is needed in this health facility to close the financial gap.